Engraftment Syndrome: A Retrospective Analysis of the Experience at a Tertiary Care Institute - Raja Pramanik; Harish Kancharla; Sameer Bakhshi; Atul Sharma; Ajay Gogia; Prabhat Malik; Ranjit Kumar Sahoo; Atul Batra; Sanjay Thulkar; Lalit Kumar (Clinical Hematology International, 2019)
Engraftment syndrome (ES) is a clinical syndrome that occurs in the early neutrophil recovery phase following hematopoietic stem cell transplant (HSCT). Although also described for allogenic HSCT, it is basically diagnosed in the context of autologous HSCT. We retrospectively reviewed 171 consecutive HSCTs performed between January 2013 and January 2015 in our Bone Marrow Transplant (BMT) unit and analyzed all cases of noninfectious fever and strong clinical features suggestive of ES in the peri-engraftment period for up to 7 days. We observed the incidence of ES to be 12.3% (16/130) in the autologous and 4.8% (2/41) in the allogeneic cohort. Among plasma cell disorders, which constitute 50% of our study population, the incidence of ES was 19.7%. Among the ES cases of autologous transplants, 81.2% (13/16) patients satisfied the Maiolino criteria (MC) and 87.5% (14/16) patients the Spitzer diagnostic criteria (SC). A total of 68.7% (11/16) patients satisfied both MC and SC, and two patients (12.5%) did not satisfy either (MC− SC−). There was no significant difference in days of hospitalization and usage of supportive care between ES and non-ES patients, and there was no mortality due to ES. On univariate analysis, female patients (p < 0.013) and those with diagnosis of a plasma cell disorder (p < 0.03) had higher risk of ES. In conclusion, the incidence of ES in our study population is consistent with that of many others, but severity evaluation needs exploration in larger cohorts with pragmatically modified diagnostic criteria.